2011
DOI: 10.1007/s13592-011-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-induced honeybee worker piping

Abstract: -The worldwide maintenance of the honeybee has major ecological, economic, and political implications. In the present study, electromagnetic waves originating from mobile phones were tested for potential effects on honeybee behavior. Mobile phone handsets were placed in the close vicinity of honeybees. The sound made by the bees was recorded and analyzed. The audiograms and spectrograms revealed that active mobile phone handsets have a dramatic impact on the behavior of the bees, namely by inducing the worker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…This similarity validates both the observed effect and the studies. Apart from effects on reproduction, many other significant effects reported in many other studies (Balmori, 2009;Cammaerts and Johansson, 2013;Cammaerts et al, 2011Cammaerts et al, , 2012Cucurachi et al, 2013;Favre, 2011) further support the observation that mobile telephony radiation adversely affects living organisms.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…This similarity validates both the observed effect and the studies. Apart from effects on reproduction, many other significant effects reported in many other studies (Balmori, 2009;Cammaerts and Johansson, 2013;Cammaerts et al, 2011Cammaerts et al, , 2012Cucurachi et al, 2013;Favre, 2011) further support the observation that mobile telephony radiation adversely affects living organisms.…”
Section: Introductionsupporting
confidence: 75%
“…In another study with bees (Favre, 2011) in which again two active mobile phones were used for exposure, Dr Verschaeve claimed that "experimental conditions did not coincide with 'normal' exposure conditions, for example, where hives are nearby a base station antenna," which is a very strange statement because (a) radiation from base stations is very similar with that of corresponding mobile phones with an intensity depending on distance (since base station antennas are about 100 times more powerful than corresponding mobile phones, an active handset at 20-30 cm distance corresponds approximately to a base station antenna at 20-30 m distance, which is realistic for base stations located in the country); (b) bees can also be exposed by people carrying their mobile phones at close proximity to the hives. (c) It is usual in experiments to employ an intensity higher than "normal" in order to observe more clearly an effect.…”
Section: The Author Neglects Important Findings While Making Unjust mentioning
confidence: 96%
“…Hymenoptera (such as bees and ants) are actually extremely sensitive. Bees (Favre, 2011;Sharma and Kumar, 2010;Harst et al, 2006;Kimmel et al, 2007;Warnke, 2009) and ants (Cammaerts et al, 2012a(Cammaerts et al, , 2013 have been demonstrated to suffer from electromagnetic waves in their environment. Ants can easily be maintained in a laboratory all over the year and can be tested at any moment in time.…”
Section: Introductionmentioning
confidence: 99%
“…These observations have to be taken cautiously as the authors did not indicate the exposure duration and did not control the age of honeybees, a critical factor. More recently, Favre (2011) introduced into the hive a mobile phone (900 MHz, energy absorption rate <2 W/kg) playing a radio station program for several hours and observed the induction of worker piping, a behaviour associated with disturbance of the hive. Although control experiments included hives without mobile phones or with mobile phones kept in standby mode, no control of the effect of the sounds emitted by the mobile phone was done.…”
Section: Discussionmentioning
confidence: 99%
“…Although a direct relationship has not been established between radio wave exposure and health problems (Krewski et al 2007;Vanderstraetan and Verschaeve 2008), behavioural and spatial memory disorders in humans (D'Andrea et al 2003;Wiholm et al 2009) and orientation disorders in honeybees and birds (Warnke 2007) have been suspected and a negative effect of radio waves on the in-hive behaviour and homing flight of honeybees has been reported (Harst et al 2006;Kimmel et al 2007). Cell phone radiations were suspected of affecting the reproductive capacity of Drosophila (Panagopoulos et al 2004) and the egg laying rate of the honeybees' queen (Sharma and Kumar 2010) and inducing the worker piping signal in the hive (Favre 2011).…”
Section: Introductionmentioning
confidence: 99%